Influence of water depth and season on the photodegradation of micropollutants in a free-water surface constructed wetland receiving treated wastewater. (November 2019) - Mathon, B.; Coquery, M.; Miège, C.; Vandycke, A.; Choubert, J.-M.
Abstract: Micropollutants such as pharmaceutical products and pesticides are still present in treated wastewater. Several of these compounds are photoactive, either by direct or indirect photodegradation. An innovative on-site experimental protocol was designed to investigate the contribution of photodegradation processes to eliminate micropolluants in constructed wetland (CW). The solar photodegradation of 23 organic micropollutants was studied using in situ photoreactors at different depths. A CW-photodegradation model was designed and calibrated to further scrutinize the contribution of direct and indirect photodegradation processes in the elimination of micropollutants. The results show that photodegradation is most effective in the first 10 cm of the water column. A classification of micropollutants in 3 groups was developed to characterize their photodegradation. A significant increase of the half-life by direct photodegradation was observed in winter compared to summer due to a lower light intensity in winter. On the opposite, for direct + indirect photodegradation, no significant difference was observed between seasons. The decrease in light intensity in winter was compensated by higher nitrates concentration which promoted the formation of hydroxyl radicals and increased indirect photodegradation. The CW-photodegradation model successfully simulated the measured concentrations for direct and indirect photodegradation for 23 micropolluants. Nonetheless, it overestimated the indirect photodegradation with hydroxyl radicals when using default parameter values derived for surface waters. Hence, the consumption of hydroxyl radicals was increased by a factor of 20 for treated water. This model highlighted the predominance of direct photodegradation in the elimination of all micropollutants, except sotalol for the winter campaign. Graphical abstract: Image 1 Highlights: Micropollutants photodegradation of treated wastewaters is effective for at least the top 10 cm. The main process in the basin of a constructed wetland is the direct photodegradation. Half-life (t1/2 ) were measured in situ for total and only direct photodegradation. t1/2 were similar for both seasons due to higher nitrates concentration in winter. The model rightly simulated micropollutants photodegradation in treated wastewaters.